Water supply & sanitation : rural and low income urban communities - Ahmed, M. Feroze; Mujibur Rahman, Md.; IRC International Water and Sanitation Centre; Bangladesh University of Engineering and Technology. Centre for Water Supply and Waste Management; ITN-Bangladesh (Network) (Dhaka : ITN-Bangladesh, Centre for Water Supply and Waste Management, BUET, 2000)
With reference to Bangladesh.
Includes bibliographical references (p. 441-442).
ARC
Keywords: Water-supply, Rural -- Bangladesh -- Management; Drinking water -- Health aspects -- Bangladesh; Public health -- Bangladesh